As propostas de autonomia mapuche no Chile do pós-ditadura (1990-2010) - Gomes, Caroline Faria (2020)
The Mapuche movement is currently a prominent social movement of indigenous origin in Chile and Latin America, composed of six main ethnic groups that mostly inhabit the southern regions of the country. The treatment directed to Mapuche by the Chilean State shows that the historical State project has not recognized the ethnic differences characteristic of the territory. On the contrary, this nation-state has sought to consolidate a homogeneous and uniform society model, generating very conflicting relations with indigenous communities, since, during its formation in the 19th century, the idea that each State should correspond to a nation proved to be imperative and imposed the systematic denial of existing ethnic diversity. One of the consequences of this denial was the creation of indigenist laws that sought to homogenize society through policies of integration and assimilation of the various ethnic groups to the hegemonic national group identified with the mixed race. The indigenous resistance to such integrative policies is also historic and has taken on different facets over the years. Since the 1990s, the main form of resistance debated among Mapuche organizations has been autonomy. We consider that the 1990s marked a new cycle of mobilizations of the contemporary Mapuche movement and represented a break with previously developed political strategies. Therefore, in this study, we analyze the autonomy projects developed by two organizations that were the protagonists of the Mapuche movement during the 1990s: the Consejo de Todas las Tierras (CTT) and the Coordinadora de Comunidades en Conflicto Arauco Malleco (CAM). In our analysis, in addition to the autonomic project, we have also sought to explain the struggle strategies employed by these organizations, as well as taking a look at the response of the governments of the Concertación de Partidos por la Democraciato the Mapuche autonomist demands. For this study, we used as sources the official communications and journals published by these organizations, in addition to extensive bibliography on the subject. In examining sources, we use elements of content analysis as our methodology.